Reverse Location of Software Online Upgrade Function Based on Semantic Guidance - Lyu, Xiao-shao; Shu, Hui; Kang, Fei; Huang, Yu-yao (Ji suan ji ke xue, 2022)
The hijacking attack for software online upgrade is one of the most common methods of network attack.Program ana-lysis is an important method to evaluate the security of software upgrade quickly and automatically.Rapid reverse positioning of upgrade functions in software is a key premise to realize static analysis and improve the efficiency of dynamic analysis.Traditional program analysis reverse localization relies on manual experience based on the cross reference chain relation of semantic information, such as string and API function, which is inefficient and cannot be automated.To solve this problem, this paper proposes a software upgrade function localization method based on semantic analysis and reverse analysis.Firstly, an upgrade semantic classification model based on natural language processing is established for common semantic information（string, function name, API function, etc.） in software binary program.Secondly, the software semantic information is extracted by reverse analysis tool, and the up